病原性細菌生育の抑制のための組成物および方法 (2024)
Methods and compositions for populating the gastrointestinal tract of a subject are described. Methods include administering to a subject a therapeutic composition comprising a purified population of spore-forming bacteria produced by providing a fecal material and subjecting the material to a treatment step resulting in purification of spore-forming bacteria. Methods include administering an amount effective to engraft and/or augment in the gastrointestinal tract in order to treat or prevent a dysbiosis in the mammalian subject.